2009
DOI: 10.2215/cjn.02420409
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Metabolism and Inflammation in Chronic Kidney Disease Patients

Abstract: Results: Patients were classified by tertiles of Ca, phosphorus (P), Ca-P product (Ca x P), and parathyroid hormone (PTH). After adjustment for age, gender, and eGFR, the levels of C-reactive protein (CRP) and IL-6 (IL-6) of the third tertile of P, Ca x P, and PTH were significantly higher than those of the first and second tertiles. Serum P and Ca x P directly correlated with CRP and IL-6, whereas HDL-cholesterol and eGFR inversely correlated with the levels of the inflammatory parameters. After partial corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 52 publications
2
61
1
2
Order By: Relevance
“…The mechanisms underlying increased risk of hospitalization associated with disturbances of mineral metabolism remain uncertain. Accumulating evidence indicates that elevated levels of serum calcium-phosphorus product and disorders of calcium homeostasis may accelerate vascular calcification and induce inflammation [41,42]. Moreover, a recent study showed that higher dialysate calcium concentration is associated with increased sympathetic activity during HD, which might lead to unfavorable outcomes [43].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying increased risk of hospitalization associated with disturbances of mineral metabolism remain uncertain. Accumulating evidence indicates that elevated levels of serum calcium-phosphorus product and disorders of calcium homeostasis may accelerate vascular calcification and induce inflammation [41,42]. Moreover, a recent study showed that higher dialysate calcium concentration is associated with increased sympathetic activity during HD, which might lead to unfavorable outcomes [43].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased serum phosphorus is an independent risk factor for the presence of a significant inflammatory state in CKD patients (14). In addition to the reduction of phosphorus levels, the noncalcium phosphate binder sevelamer has been associated with anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, serum phosphorus is direct and independently correlated with inflammatory parameters, indicating that hyperphosphatemia may be a contributing factor to inflammation (14). Therefore, adequate management of hyperphosphatemia is a critical issue in renal patients.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, altered phosphate metabolism is associated with age-related changes, inflammation, and death in chronic kidney disease (190,300), and in young healthy subjects serum phosphorus content is associated with coronary atherosclerosis later in life (139).…”
Section: (See the Role Of Sirtuins In Cr)mentioning
confidence: 99%